RGB1 Regulates Grain Development and Starch Accumulation Through Its Effect on OsYUC11-Mediated Auxin Biosynthesis in Rice Endosperm Cells - Zhang, Dongping; Zhang, Minyan; Liang, Jiansheng (Frontiers in Plant Science, 2021)
RGB1, a subunit of heterotrimeric G protein, plays important roles in regulating grain size and weight of rice. However, the molecular mechanisms underlying controlling grain filling process by G protein are still largely unclear. In the present study, we show that RGB1 controls not only the grain size but also the grain filling process. Knock-down of RGB1 significantly delayed grain development and reduced starch accumulation and grain weight, which was closely related to the delayed and the lower expression of genes encoding sucrose metabolism and starch biosynthesis related enzymes during grain filling stage. Suppression of RGB1 expression also resulted in the lower auxin content in grains, which was correlated with the lower expression of OsNF-YB1 and OsYUC11 during grain filling stage. Further biochemical evidence showed that OsYUC11 expression was under control of OsNF-YB1 by its interaction with promoter of OsYUC11. Taken together, we propose that RGB1 controls rice grain development and grain filling process by changing auxin homeostasis in endosperm cells. OsNF-YB1, which acts as a key downstream effector of RGB1, interacts directly with the promoter of OsYUC11 and stimulates the OsYUC11 expression, thereby regulating auxin biosynthesis and starch accumulation and grain size.